Is heavy binge-watching a socially driven behaviour? Exploring differences between heavy, regular and non-binge-watchers. (1st June 2022) - Anghelcev, George; Sar, Sela; Martin, Justin; Moultrie, Jas L.
Results of an online survey suggest that heavy binge-watching of serialized video content might be in part socially motivated. Among a sample of US college students, heavy binge-watchers were more likely to be opinion leaders and to experience fear of missing out (FOMO) than regular binge-watchers or non-binge-watchers. They also reported higher levels of parasocial engagement with the shows' characters than other viewers. Contrary to common beliefs, heavy binge-watching did not come at the cost of decreased social engagement. Quite the opposite: heavy binge-watchers reported spending significantly more time in interactions with friends and family on a daily basis than non-binge-watchers. Heavy binge-watching was also modestly associated with a few negative outcomes (loss of sleep and decrease in productivity).